ANALISIS EKONOMI DAN KELAYAKAN LINGKUNGAN PENERAPAN GREEN SUPPLY CHAIN MANAGEMENT (GSCM) PADA PRODUKSI SUSU - Ida Bagus Suryaningrat; Elida Novita; Rika Dwi Kurniaputeri (AGROINTEK, 2020)
In milk processing, supply chain activities were started fromthe procurement of raw materials, milking cows, milkprocessing, marketing of dairy products, and wastemanagement. The purposes of this study were to analyzeeconomical aspect, and to study environmental aspect onGSCM implementation in CV. MUER. Direct survey anddisccussion, environmetal indicators and economicalanalysis were implemented in this study. The results of studyfound that the use of water for cage cleansing was 3600liters, number of feeding was 2265.57kg, milking productionwas 550 liters, the water usage for washing tools was 250liters. The assessment of environmental indicators using 13indicators found that this unit has score of 30 means thatCV. MUER has implemented most of the GSCM conceptsalong the supply chain of milk production. Other resultshowed that the amount of contamination (COD and BODvalue) in the milk processing was higher than govermentregulation standard. In term of economical analysis shownthat NPV value was Rp.2.723.162.185, IRR 36.99%, and B /C ratio was 1.48. This means that the value of NPV wasgreater than zero, IRR was greater than the bank interestrate (equal to 10%), and B/C ratio was greater than 1, thisindicated that based on environmental and economicalaspect, GSCM has a high feasibility to be implemented inCV. MUER.In milk processing, supply chain activities were started fromthe procurement of raw materials, milking cows, milkprocessing, marketing of dairy products, and wastemanagement. The purposes of this study were to analyzeeconomical aspect, and to study environmental aspect onGSCM implementation in CV. MUER. Direct survey anddisccussion, environmetal indicators and economicalanalysis were implemented in this study. The results of studyfound that the use of water for cage cleansing was 3600liters, number of feeding was 2265.57kg, milking productionwas 550 liters, the water usage for washing tools was 250liters. The assessment of environmental indicators using 13indicators found that this unit has score of 30 means thatCV. MUER has implemented most of the GSCM conceptsalong the supply chain of milk production. Other resultshowed that the amount of contamination (COD and BODvalue) in the milk processing was higher than govermentregulation standard. In term of economical analysis shownthat NPV value was Rp.2.723.162.185, IRR 36.99%, and B /C ratio was 1.48. This means that the value of NPV wasgreater than zero, IRR was greater than the bank interestrate (equal to 10%), and B/C ratio was greater than 1, thisindicated that based on environmental and economicalaspect, GSCM has a high feasibility to be implemented inCV. MUER.